Activation of the β‐common receptor by erythropoietin impairs acetylcholine‐mediated vasodilation in mouse mesenteric arterioles. Issue 12 (25th June 2018) - Kilar, Cody R.; Diao, YanPeng; Sautina, Larysa; Sekharan, Sivakumar; Keinan, Shahar; Carpino, Bianca; Conrad, Kirk P.; Mohandas, Rajesh; Segal, Mark S.
Abstract: Clinically, erythropoietin (EPO) is known to increase systemic vascular resistance and arterial blood pressure. However, EPO stimulates the production of the potent vasodilator, nitric oxide (NO), in culture endothelial cells. The mechanism by which EPO causes vasoconstriction despite stimulating NO production may be dependent on its ability to activate two receptor complexes, the homodimeric EPO (EPOR2 ) and the heterodimeric EPOR/ β ‐common receptor ( β CR). The purpose of this study was to investigate the contribution of each receptor to the vasoactive properties of EPO. First‐order, mesenteric arteries were isolated from 16‐week‐old male C57BL/6 mice, and arterial function was studied in pressure arteriographs. To determine the contribution of each receptor complex, EPO‐stimulating peptide (ESP), which binds and activates the heterodimeric EPOR/ β CR complex, and EPO, which activates both receptors, were added to the arteriograph chamber 20 min prior to evaluation of endothelium‐dependent (acetylcholine, bradykinin, A23187) and endothelium‐independent (sodium nitroprusside) vasodilator responses. Only ACh‐induced vasodilation was impaired in arteries pretreated with EPO or ESP. EPO and ESP pretreatment abolished ACh‐induced vasodilation by 100% and 60%, respectively. EPO and ESP did not affect endothelium‐independent vasodilation by SNP. Additionally, a novel β CR inhibitory peptide ( β IP), which was computationally developed, prevented the impairment of acetylcholine‐induced vasodilation by EPO and ESP, further implicating the EPOR/ β CR complex. Last, pretreatment with either EPO or ESP did not affect vasoconstriction by phenylephrine and KCl. Taken together, these findings suggest that acute activation of the heterodimeric EPOR/ β CR in endothelial cells leads to a selective impairment of ACh‐mediated vasodilator response in mouse mesenteric resistance arteries. Abstract : The mechanism by which EPO causes vasoconstriction despite stimulating NO production may be dependent on its ability to activate two receptor complexes, the homodimeric EPO (EPOR2 ) and the heterodimeric EPOR/ β ‐common receptor ( β CR). The purpose of this study was to investigate the contribution of each receptor to the vasoactive properties of EPO. Our findings suggest that acute activation of the heterodimeric EPOR/ β CR in endothelial cells leads to an impairment of ACh‐mediated vasodilator response in mouse mesenteric resistance arteries.